PENERAPAN METODE MATHERNAL REFLEKTIF DALAM PEMBELAJARAN BERBAHASA PADA ANAK TUNARUNGU DI KELAS PERSIAPAN SLB NEGERI SEMARANG - Linawati, Ririn (Indonesian Journal of Early Childhood Education Studies, 2012)
Children, who experience in their highest potensial, need many chances for study in the environment that include all knowledges. Language is the important factor for humanâs communication, studying, and socialization. But, no every child ability speak easily. It can be caused by genetic factor, like deaf children. Therefor, deaf children need good language studymethod that can make them easy for studying language. SLB N Semarang is the one of school that applying that method for a long time. Because of that reality, researcher decides that the purpose of this research is knowing about application ofÂ  Reflective Maternal Method (MMR) for deaf child in readiness class SLBN Semarang. This research is qualitative research. The research is done in SLBN Semarang and use many teachers, who teaching deaf child in readiness class, for get many informations. Method for collecting data in this research are interview, observation, and documentation. Data analysis is using trianggulasi. This research is showing that the application of MMR for deaf children is well done. MMR carried out with three stages, that are planning, doing,Â  and evaluating. That stages are done for achieve every target of the goals. This process has fulfilled the guide of MMRâs application. This research find that government not make curriculum or rule yet for deaf children in school. The researcher make suggestion for government to decide curriculum and clearly guide about deaf childrenâs study or deaf children study method with MMR. So that, the application of Reflective Maternal Method (MMR) for deaf children can achieve the goals and increase the childrenâs ability.